2012
DOI: 10.1071/mu12026
|View full text |Cite
|
Sign up to set email alerts
|

A review of flight-initiation distances and their application to managing disturbance to Australian birds

Abstract: 26

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
214
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(225 citation statements)
references
References 79 publications
9
214
1
1
Order By: Relevance
“…Estimates of FID have significant ramifications for management of shorebird and waterbird breeding and stopover habitat , Koch and Paton 2014, Rodgers and Smith 1995, Weston et al 2012a). The median FID we documented when birds were disturbed by walkers or boats (~40 m) is similar to distances reported in previous studies (e.g., Blumstein 2003, Burger and Gochfeld 1991, Thomas et al 2003, but less than values reported for some larger species of shorebirds documented in other areas (e.g., Koch and Paton 2014), perhaps due to different methods of observation and analysis between studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimates of FID have significant ramifications for management of shorebird and waterbird breeding and stopover habitat , Koch and Paton 2014, Rodgers and Smith 1995, Weston et al 2012a). The median FID we documented when birds were disturbed by walkers or boats (~40 m) is similar to distances reported in previous studies (e.g., Blumstein 2003, Burger and Gochfeld 1991, Thomas et al 2003, but less than values reported for some larger species of shorebirds documented in other areas (e.g., Koch and Paton 2014), perhaps due to different methods of observation and analysis between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Avian use of critical habitats such as these can be impacted by a variety of anthropogenic factors (Glover et al 2011, Madsen 1995, Weston et al 2012a. Birds typically exhibit a flight response when approached by humans.…”
Section: Introductionmentioning
confidence: 99%
“…The distance at which recommendations for standard data collection have been made (Weston et al 2012).…”
mentioning
confidence: 99%
“…FID is a common measure of the bird response to human disturbance or predation risk (Weston et al, 2012), and it is directly related with the remaining time to escape from the approaching train. We used the poles supporting the catenary, which are 60 m apart, as a distance reference.…”
Section: Methodsmentioning
confidence: 99%